Influence of additive contents on the properties of SiC ceramic membranes and their performance in oil‐water separation. Issue 3 (24th January 2023) - Das, Dulal; Kayal, Nijhuma
Abstract: The high processing cost is the key challenge for the economic industrial use of SiC membrane The aim of this research was to fabricate mullite bonded porous SiC ceramic membrane at low temperature from novel combinations of fly ash and alumina (FA) in weight ratio 44.5:55.5 as sintering additives. The influences of FA and pore former content on the porosity, morphology, crystalline phase composition, mechanical performance, permeability properties were investigated. The membrane prepared at 1300°C using 20 wt% FA showed pure water permeability 3690 Lm −2 h −1 bar −1 and exhibited high oil removal efficiency of ∼ 98% from the synthetic oil‐water emulsion having oil concentration of 1000 mg/L. The corrosion behaviour of silicon carbide membrane in the strong acid and alkali solution and its mechanism were investigated. The utilization of fly ash successfully reduced the raw material cost and sintering temperature and the use of alumina reduced the amount of oxidation of SiC as well as increased the amount of mullite bond phase which resulted excellent mechanical strength to the final ceramics.